Impact of 2015 Earthquake on Educational Attainment of Children in Nepal (Quest Journal of Management and Social Sciences, 2022)
Background: Natural disaster has far-reaching consequences on the economic development of low-income economies due to the damage to physical and human capital and their poor resilience toward such damages. Nepal faces such disasters at frequent intervals without much effort to account for its consequences, particularly on human capital.Objective: This study assesses the short-term impact of Nepal's 2015 earthquake on children's educational attainment. The study also conducts heterogeneous analysis to analyze how the impact varies by gender. Secondary school completion is chosen as a measure of educational attainment.Method: The study utilizes second and third rounds of household survey data taken from the Nepal Risk and Vulnerability Survey (NHRVS) conducted by the World Bank. The study uses child fixed effects combined with the difference-in-difference method to account for issues relating to identifying the earthquake's impact on educational attainment.Results: The study finds that the cohorts exposed to the earthquake had an adverse effect on the probability of secondary school completion. A heterogeneous analysis by gender further reveals that the male children experienced a significant drop in their secondary school completion probability while female children essentially had no impact.Implication: The quality of human resources depends upon the quality of health and education in any country. The findings of this research draw the attention of the policymakers to the serious consequences that natural disaster has on human capital and help make informed policy decisions not only during the recovery process but also during the planning and policy formulation stage.Originality: This paper is original and has not been published anywhere else.